THE EVOLUTION OF INTELLECTUAL CAPITAL IN KNOWLEDGE MANAGEMENT: A GLOBAL SYSTEMATIC LITERATURE REVIEW STUDY ON PUBLIC ORGANISATIONS - Havidotinnisa, Siti; Rofaida, Rofi; Hadijah, Hady Siti (Multifinance, 2025)
This study aims to analyze the evolution of intellectual capital in public organization knowledge management globally, focusing on the period 2000–2025, to identify current trends, challenges, and best practices. This study uses a systematic literature review (SLR) method based on the PRISMA protocol, analyzing 10 articles indexed in Scopus and Web of Science. The research findings reveal three main findings. First, human capital in public organizations has undergone digital transformation, where technology-based competencies such as data analytics and AI have become critical, although skill gaps remain a challenge, particularly in developing countries. Second, structural capital is rapidly developing through the adoption of cloud-based knowledge management systems, blockchain, and collaborative platforms, but is hindered by rigid bureaucracy and infrastructure limitations in some regions. Third, relational capital is strengthened by social media and digital public participation mechanisms, although it is vulnerable to misinformation. This study also identifies the emergence of the concept of “green intellectual capital,” which integrates sustainability principles into the three dimensions of intellectual capital. Theoretically, these findings enrich the discourse on intellectual capital by integrating the perspectives of the Knowledge-Based View, Institutional Theory, and Complexity Theory. Practically, this study recommends accelerating digital training for public human resources, standardizing the interoperability of knowledge systems, and strengthening technology-based multisectoral collaboration. Policy implications include the need for a regulatory framework that supports intellectual capital innovation while addressing the challenges of the digital divide and knowledge governance.